The agitators : three friends who fought for abolition and women's rights - Wickenden, Dorothy (Scribner, 2021)
Chronicles the revolutionary activities of Harriet Tubman, Frances Seward, and Martha Wright--friends and neighbors in Auburn, New York--discussing their vital roles in the Underground Railroad, abolition, and the early women's rights movement.